DIRECTIONS OF IMPROVEMENT OF THE LEGISLATION OF UKRAINE ON PROTECTION OF INTELLECTUAL PROPERTY RIGHTS IN THE SPHERE OF SPACE ACTIVITY - Боричевський, В. М. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2007)
This article discusses the problems of intellectual property rights protection in the field of space activities in Ukraine and proposes ways to solve them at the legislative level.